Characteristics of Innovation in Regions with Small- and Medium- Sized Towns - Zoltán Birkner; Tivadar Máhr; Erzsébet Péter; Nora Rodek Berkes (Naše gospodarstvo/Our economy, 2018)
Globalisation “takes” its victims, which the authors believe means that the future of small- and medium-sized towns has become uncertain in Europe. The role of centres is continuously increasing, and most researchers prefer to analyse the competitiveness and innovativeness of metropolitan areas. In this study, we characterise the small- and medium-sized towns in the central–eastern European region as well as explore their possible development path. The authors are convinced that one way for these towns to survive is through strengthening of innovation abilities, which means increasing the innovation performances of economic stakeholders and new forms of interaction among other institutions in order to handle social problems. The theoretical starting point is the interpretation and presentation of the micropolitan (without big towns) regions as well as understanding the concept of technological and social innovation. As the result of the research, the innovation measurements carried out in some of the settlements will be represented. These experiences can help the small- and medium-sized towns keep up with global competition and cancel migration and erosion of intellectual potential.